(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Kerala’s leading traditional industry is handloom. Since the beginning of time, Kerala has been home to a large number of looms, and even in the early nineteenth century, a facility for handloom production operated here. Despite having an absolutely fantastic future and a huge potential for employment, this business currently faces a significant amount of challenges in addition to contributing to the GDP of the nation. This paper takes a critical look at the issues and challenges facing this business in this setting and offers some solutions and policy options.